A fluorescence resonance energy transfer‐based assay to study SUMO modification in solution - Bossis, Guillaume; Chmielarska, Katarzyna; Gärtner, Ulrike; Pichler, Andrea; Stieger, Evelyn; Melchior, Frauke (Ubiquitin and protein degradation ; A: Ubiquitin and protein degradation, 2005)
Analysis of posttranslational modifications with ubiquitin and ubiquitin‐related proteins (Ubl) generally involves detection of the modified species by immunoblotting or autoradiography, techniques that are not easily applicable for kinetic, quantitative, or high‐throughput assays. To circumvent these limitations for studies on ubiquitin‐related proteins of the SUMO family, we have developed a fluorescence resonance energy transfer (FRET)‐based assay system using yellow fluorescent protein (YFP)‐tagged mature SUMO1 (amino acids 1-97) and cyan fluorescent protein (CFP)‐tagged RanGAP1 (amino acids 400-589) as model substrates. Reactions are set up in 384‐well microtiter plates and are followed online using a fluorescence microtiter plate reader. Applications may involve identification and analysis of SUMO‐modifying enzymes and isopeptidases, comparison of enzyme and substrate mutants, and screens for small molecular weight inhibitors. The principal outline of the assay should be applicable to other Ubl conjugation systems as well.